Assessing artificial lighting performance using DIALux in heritage buildings (ARTEKS : Jurnal Teknik Arsitektur, 2025)
This study aims to turn on artificial outdoor lighting in the State Electricity Company (PLN) Building as a cultural heritage building in the Kayutangan Heritage Area using DIALux Evo simulation with input measurements and observations in the field. This simulation assesses the average lighting level, lighting uniformity, and energy efficiency, with comparisons to national and international standards. The focus of the study includes the average illumination value, lighting uniformity, and glare assessment which will later be developed into the principle of intelligent lighting in preserving cultural heritage buildings. Based on the simulation results, it was found that most areas of the building have lighting levels below SNI standards, especially in outdoor/pedestrian areas (horizontal elements) and facades (vertical elements). The overlay graph shows a significant disparity in light distribution. These results indicate the need for lighting design interventions in pedestrian areas and building facades. The development of lighting design can later be in accordance with considering aspects of surface materials, functionality, energy efficiency, and most importantly, it can support aspects of preserving cultural heritage buildings. This research is expected to be the basis for developing sustainable lighting strategies in cultural heritage buildings, especially in the Kayutangan Area.
Keywords: Artificial lighting; DIALux simulation; Heritage buildings; Kayutangan heritage